RELATIONSHIP OF ISOLATION TO LUXURY BRAND PURCHASE TENDENCY: MODERATING ANXIETY AND SOCIAL CAPITAL EFFECT FROM COVID-19 - Refani Hedilis; Evo Sampetua Hariandja (Faculty of Economics and Business Universitas Pelita Harapan, 2023)
The aims of this study is to explore the effect of COVID-19, especially the isolation period on luxury brand purchase tendency. The data was collected from 350 respondents by distributing questionnaires of 35 questions or indicators. From eight hypotheses that have been formed, there are 6 supported hypotheses and 2 unsupported hypotheses. The sample for this study involves respondents who are dominated by luxury brand consumers who are in the Jakarta area with the age of 18-25 years old. The insights provided by this study are useful to determine the moderating effect of anxiety and social capital from COVID-19. This study also written to complete previous researches that are still very minimal, especially in terms of discussing the effects of social capital itself. The study contributes to explain the impact by focusing on the purchase of luxury goods by various age group living in Jakarta area. Further, this study also explores some of the hypothesis from previous studies that are related to luxury consumptions and pandemic effect on purchasing tendencies. It enhances the understanding of the impact of COVID-19 on the purchase of luxury goods.